Physical activity in college students before and during the COVID-19 lockdown - Alarcón Tenorio, Alexander (2023)
COVID-19 lockdown has changed student’s lifestyle, especially the physical activity (PA) as many students remained at home with limitations to perform PA. Objective: To determine the level of physical activity of private university students before and during lockdown due to COVID-19 pandemic. Methods: A cross-sectional study was performed including all pre-graduated students of the Public Health and Administration Faculty (N=161) invited by e-mail.  To measure the level of PA before and during the lockdown, a short version of the questionnaire IPAQ was applied via Google Forms. Results: The answer rate was 56.5% (n=91). A significant reduction in PA before and during lockdown was observed, values were 55.6%, 10.9% and 11.1% for the high, intermediate, and low levels of PA. The number of students that performed PA based on WHO’s recommendation decreased from 36 to 23 (36.1%). Conclusions: The lockdown impacted negatively in the intensity and frequency of PA based on WHO’s recommendations.